Implications of Marriage by Accident - Fathur, KM. Al Fathur Ikhsan (State of Islamic Institute Langsa, 2023)
Sudden marriage or married by accident often occurs in adolescents at the age of less than 20 years because they have become pregnant first. Pregnant mating is caused by various internal and external factors. One of the internal factors is weak faith and external factors such as promiscuity. At a young age having married and becoming pregnant from these actions there are implications for married couples. This article is classified as a literature research with a qualitative approach. The methodology used is the study of descriptive analysis by considering juridical, psychological, and sociological (interdisciplinary) aspects. The results of the study concluded that; Juridically, marriages due to incidents of extramarital pregnancies may be performed. Psychologically, the marriage had an impact on unstable emotions. Sociologically, maternity marriage has an impact on age gaps, job opportunities, and negative impressions by society.